Crossing the Rubicon : the shaping of India's new foreign policy - Raja Mohan, C. (New Delhi ; New York : Viking, 2003)
Covers the post-1980 period.
Includes bibliographical references (p. [273]-312) and index.
Keywords: India -- Foreign relations -- 1984-